Effect of PEDOT:PSS Coating on Manganese Oxide Nanowires for Lithium Ion Battery Anodes. (1st January 2016) - Ko, In-Hwan; Kim, Seong-Jun; Lim, Joohyun; Yu, Seung-Ho; Ahn, Jihoon; Lee, Jin-Kyu; Sung, Yung-Eun
Abstract: Transition metal oxides have been considered as promising lithium storage materials that undergo a conversion reaction, exhibiting high specific capacity. However, capacity fading during cycling is the most serious obstacle for their commercialization. In order to overcome this, we have added PEDOT:PSS (poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate) to Mn2 O3 nanowires. PEDOT:PSS was successfully coated onto Mn2 O3 nanowires while maintaining the structure of Mn2 O3 . The coating of PEDOT:PSS reduced the resistance of the surface and protected the surface electron channels from the pulverization effect of the charge–discharge operation. α-Mn2 O3 /PEDOT:PSS showed excellent cyclability with a reversible capacity of 1450 mAh g −1 after 200 cycles at a current density of 100 mA g −1 . An increase in capacity was observed with continuous cycling, which may be attributed to further oxidation of the manganese species and a reversible reaction of the gel-like polymer on the manganese surface. The results demonstrate that PEDOT:PSS enhances the electrochemical activity by providing electron channels and prevents pulverization caused by the charge and discharge process.